Small and Medium Business Management Small and Medium Business Management-Financial Sources and Difficulties - Eniola, Anthony A.; Harry, Entebang (SciPress Ltd, 2015)
SMEs has performed an unparalleled role in coming to the Nigeria economic growth and assist as a training ground for entrepreneurs and a provider of solutions to address the challenges of unemployment in all consuming labours and promoting marketing growth. An opportunity for the wholesome advancement of SMEs in Nigeria was in connection to the sea change and growth policy as a consequence of the rapid advancement of the global economic system. But with the world economic unification, SMEs business environment is facing tremendous changes and more intense competition. Hence, the reason for this study is to confront the sources of SME firm financing, conceptualise its financial challenges and source causes with objectives to exploit the increase and advancement of SMEs prospectively.